Auto Regressive Integrated Moving Average (Arima)model for Forecasting the Production, Export and Import of Wood Based Panel in India - Upadhyay, V. K.; Mohanty, B. N.; Nandanwar, Anand; Uday, D. N.; Kamath, Ravikala (Indian Forester, 2017)
This study provides a brief overview of wood based panel's production, export and import of India during the year 1990 to 2013. India has produced 39.14 million m3 wood based panels accounting to 0.79% of the global share. The major importing countries of wood based panels from India are UAE, USA, Turkey, Sri Lanka, Bangladesh, Saudi Arab and Nepal and major exporting countries to India are Malaysia, China, Indonesia, Thailand and Bhutan. The current scenario shows that production of Indian wood-based panel was 3.39 million m3 in 2013 and compound annual growth rate (CAGR) is 10.52% during 1990-2013. The CAGR on import of wood based panels during 1990-2013 was 24.54% (Quantity) and 25.1% (Value) whereas Export was 9.66% (Quantity) and 11.97% (Value). In this study ARIMA (0,1,2) with R2: 0.95 for the production, MA(2) with R2: 0.50 for the export and ARIMA (0,1,2) with R2: 0.93 for the import were found to be suitable models for forecasting. From the analysis it has been estimated that India will be producing 5.16 million m3 of wood based panels whereas import is expected at 1.87 million m3 and the export will be 0.239 million m3 by the year 2020.